PERAN EKSTRAKULIKULER HIZBUL WATHAN DALAM MEMBENTUK KARAKTER NASIONALISME RELIGIUS PADA SISWA - Anggraini, Dina Putri; Dartim, Dartim (PAI RAFAH, 2023)
Hizbul Wathan is a scouting movement founded by K.H Ahmad Dahlan as a forum for preparing and developing children, teenagers, and young people to have mental, faith, knowledge, technological, and morals to become true muslim and ready to become a cadre of the organization, people and nation. The purpose of this study is to know information about the extracurricular role of Hizbul Wathan (HW) in forming the character of religious nationalism in Muhammadiyah 3 Surakarta Senior High School Students. The research is a type of qualitative research using a phenomenological approach method. Technique collection data uses the method of observation, interviews, and documentation. The research was conducted at the HW scouting extracurricular activity at Muhammadiyah 3 Surakarta High School, which was the subject of this research the hizbul wathan coach, teacher, wakakurikulum, and also 5 students. The result of the research is;1) HW scout members do not yet have a complete of nationalism, 2) The extracurricular role of Hizbul Wathan in shaping the character of religious nationalism is through routine activities carried out by HW members, this character will slowly be formed, 3) The inhibiting factors for cultivating the character of religious nationalism through Hizbul Wathan extracurricular activities in Muhammadiyah 3 Surakarta High School students come from internal and external factors.